Interhemispheric Brain Communication and the Evolution of Turn-Taking in Mammals - Ravignani, Andrea; Lumaca, Massimo; Kotz, Sonja A. (Frontiers in Ecology and Evolution, 2022)
In the last 20 years, research on turn-taking and duetting has flourished in at least three, historically separate disciplines: animal behavior, language sciences, and music cognition. While different in scope and methods, all three ultimately share one goal—namely the understanding of timed interactions among conspecifics. In this perspective, we aim at connecting turn-taking and duetting across species from a neural perspective. While we are still far from a defined neuroethology of turn-taking, we argue that the human neuroscience of turn-taking and duetting can inform animal bioacoustics. For this, we focus on a particular concept, interhemispheric connectivity, and its main white-matter substrate, the corpus callosum. We provide an overview of the role of corpus callosum in human neuroscience and interactive music and speech. We hypothesize its mechanistic connection to turn-taking and duetting in our species, and a potential translational link to mammalian research. We conclude by illustrating empirical venues for neuroethological research of turn-taking and duetting in mammals.